Molecular Docking studies of Synthetic and Natural compounds against cFLIP protein in cancer - C. Nagamani, K. Devi, G. Sridharbabu, Vadlakonda Rajashekar, Sreenivas Enaganti (Journal of Applied Pharmaceutical Science, 2017)
Cellular FLICE – inhibitory proteins (c-FLIP) plays a major role in apoptosis. There are a few diseases reported which are associated with the apoptosis mechanism such as autoimmunity, AIDS and cancer. In majority of the cancers the c-FLIP over expression is seen. The aim of the present investigation is to evaluate a ligand / drug molecule which could resist the over expression of the c-FLIP and hence establishing itself as the major therapeutic drug target. In this quest, the docking of the c-FLIP with 28 ligands on GOLD software was performed. The docking results were found to be very encouraging with doxorubicin elevating itself as the ace ligand with the highest fitness score of 55.81.
Keywords: Apoptosis, Autoimmunity, Cancer, c- FLIP, Docking, GOLD etc.